Design thinking in science education during the last six years: A bibliometric analysis - Fatkhurrohman, Mukhammad Aji; Hamidah, Ida; Suhandi, Andi; Samsudin, Achmad (Indonesian Journal of Science and Mathematics Education, 2024)
Design thinking holds significant potential to drive innovation in science education, helping to address complex challenges and advance technological and industrial development. This study aims to analyze trends and research opportunities in design thinking within science education from 2018 to 2023 using a bibliometric approach. Data from 997 articles indexed in Google Scholar were collected through the Publish or Perish application and analyzed using VOSviewer. The results indicate a decline in the number of publications during the study period, although high research activity was recorded in 2018 and 2019. However, opportunities to integrate design thinking with interdisciplinary concepts, such as innovative teaching methods, remain significant. Therefore, the implementation of design thinking in science education can open avenues for broader innovation in teaching and learning. This study implies an enhancement of science education through the integration of design thinking, offering strategic directions for future research and practical applications in curriculum and pedagogy development.